2017
DOI: 10.18006/2017.5(2).242.257
|View full text |Cite
|
Sign up to set email alerts
|

Studies on endophytic Burkholderia sp. from sugarcane and its screening for plant growth promoting potential

Abstract: KEYWORDS Burkholderia MALDI-TOF MS Plant growth promotion Phylogeny ABSTRACTThe occurrence of Burkholderia genus as plant endophyte indigenous to locally cultivated sugarcane crop was studied. Totally 22 endophytic isolates were obtained from TB-T medium plates of which 10 were found to be putatively endophytic in sugarcane. The morphological, biochemical and MALDI-TOF MS analysis were done and 5 endophytic Burkholderia sp. isolates were identified. Among them, the isolate Burkholderia sp. ES4 shown maximum; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Considering the threat that herbicide adversely affects the production of legumes on one hand and herbicide tolerant soil microflora may enhance the legume production even under herbicide stressed soil, on the other hand, the current research was designed. Although, B. cepacia is a known pathogen, yet, it also has some agronomic importance and have previously been used as a PGPR due largely to its nitrogen fixing, phosphate solubilizing and ACC deaminase activity (Sandanakirouchenane et al 2017;Rahman et al 2017;Arthee and Marimuthu 2017) for enhancing the production of crops. For instance, B. cepacia as biofertilizer have been applied to protect crops from damaging impact of fungal pathogens leading eventually to the increase in crop yields (Holmes et al 1998).…”
Section: Herbicide and Inoculation Impact On Chemical And Biological mentioning
confidence: 99%
“…Considering the threat that herbicide adversely affects the production of legumes on one hand and herbicide tolerant soil microflora may enhance the legume production even under herbicide stressed soil, on the other hand, the current research was designed. Although, B. cepacia is a known pathogen, yet, it also has some agronomic importance and have previously been used as a PGPR due largely to its nitrogen fixing, phosphate solubilizing and ACC deaminase activity (Sandanakirouchenane et al 2017;Rahman et al 2017;Arthee and Marimuthu 2017) for enhancing the production of crops. For instance, B. cepacia as biofertilizer have been applied to protect crops from damaging impact of fungal pathogens leading eventually to the increase in crop yields (Holmes et al 1998).…”
Section: Herbicide and Inoculation Impact On Chemical And Biological mentioning
confidence: 99%
“…Through the pot experiment results, following trends can be drawn: (1) In the absence of using chemical N, P fertilizers, both strains of bacteria had good effects on all parameters compared to the treatment without using bacteria. (2) The fertilization level of 25% N and P fertilizers in combination with bacteria did not have a significant effect on the growth and yield of sugarcane, so these treatments were reduced in the field experiment later. (3) CT4bd strain, when used in combination with N, P fertilizer, increased stem diameter, degree Brix and commercial cane sugar.…”
Section: Pot-experimentsmentioning
confidence: 99%
“…The field experiment results indicated that for the sugarcane variety K95-156 grown on gray soil in Tay Ninh province, both bacterial strains CT4bd (Serratia oryzae) and TPD3b (Bacillus subtilis) had capacities of promoting plant growth under field condition and could be summarized as following: (1) The strain CT4bd combined with 75 -100% N, P fertilizers had good performance on internode number, cane yield, degree Brix , CCS and sugar yield; (2) The strain TPD3b combined with 75 -100% of N, P fertilizers had good effects on parameters including internode number, degree Brix and CCS; (3) The combination of 2 strains CT4bd and TPD3b combined with 75% of N, P fertilizers had good effects on indicators of internode index, Brix degree, sugar content and actual sugar yield.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations